Analisis dan Perancangan Sistem Informasi Pengelolaan Mutabaah Siswa (Studi Kasus : Pendidikan Al-Qur'an di SDIT Madani Ekselensia Sidoarjo) - Afifah Qonita; Aditya Rachmadi; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
SDIT Madani Ekselensia is an integrated Islamic primary school that offers education of the Qur'an as its flagship program. In the teaching of the Qur'an in SDIT Madani Ekselensia, teachers should record, remember and evaluate the progress of learning of Qur'an students individually using mutabaah. The recording of student progress is still in manual form with the teacher writing his or her assessment on the student's mutabaah sheets stored in each class. Activities on learning the Qur'an include noting the progress of students and report it to parents every day. Teachers also recapped student's mutabaah for the coordinator. The purpose of this research is to analyze and design a Student Mutabaah Management Information System using Ripple method and Problem Pyramid tool with test of analysis result and design using Consistency Analysis and Traceability Matrix. The final result of this research is use case, activity diagram, class diagram, sequence diagram, communication diagram, database schema, dan user interface sketches.